Development of the Theoretical framework for university training on education: some clues to understand its implications - Toledo Lara, Gustavo (2019)
This article presents a qualitative analysis regarding the possible implications of the development of the theoretical framework for university training on education. On the basis of the theoretical research, the need to recognize the context in which the students' research experience takes place is identified, apart from recognizing and differentiating the components of the theoretical framework. All of the above should be based on the promotion of critical thinking and argumentative capacity from the beginning of the university studies in order to develop a critical and reflective capacity so that it can be extrapolated in the future teaching action in the classroom. The tutorial action, the hypothesis of progression and the curriculum design must allow the establishment of strategies that improve the personalized attention of the students once they begin their research experience. Finally, training is crucial both for the teacher who guides the future educators and for the students themselves, since motivation and the strengthening of the teaching vocation are binding elements when it comes to integrating the skills pertaining to the professionals of the twenty-first century, more so when it comes to the teaching discipline as a field of study and training.